Microalgae-based bioremediation of reverse osmosis concentrate (ROC): Mechanisms, techno-economic bottlenecks, and circular bioeconomy perspectives - Na-Hui Hao; Jun Li; Ya-Rong Qi; Zhuo Chen; Yu-Ming Wang; Yu-Jia Gao; Xu-Cheng Cai; Yu Hong; Hong-Ying Hu; Yin-Hu Wu (Desalination, 2026)

Synergistic room-temperature NH3 sensing: TiO2/g-C3N4 heterojunction with UV-enhanced performance for food freshness monitoring - Haineng Bai; Chenjie Wang; Yang Yu; Yiru Chen; Cheng Feng; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Sihua Zhou; Fuqiang Guo; Qingfeng Li; et al. (Chemical Engineering Journal, 2026)

Rapid prediction of 6-DOF ice-floe motion using a time-embedded Bi-LSTM network - Tongqiang Yu; Longyu Wang; Chenxiao Dai; Kun Liu; Rong Wang; Huarong Cheng (Ocean Engineering, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Inkjet-printed multilayer interface engineering for hydroxide regulation and neutral-pH NiO-based urea oxidation - Yun-Hsuan Yao; Zih-Rong Syue; Yu-Ting Cheng; Hsiao-En Tsai; Yih-Sharng Chen (Chemical Engineering Journal, 2026)

A GPC3 antigenic peptide based nanovaccine to potentiate immunotherapy of hepatocellular carcinoma - Yang Qin; Longtianyang Lei; Chaoyi Liu; Chonghao Liao; Zhenghao Tao; Yao Cheng; Qing Gao; Runshu Fu; Zhuoyi Rong; Haitao Zhang; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2026)

Unveiling dynamic membrane functions in a high-rate anaerobic mesophilic co-digestion system treating cow manure and food waste: Performance, digestate characteristics, and microbial community - Hao-Cheng Zhang; Liguo Wan; Yule Han; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Bioresource Technology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

First case report: Severe mass mortality in intensively cultured black scraper (Thamnaconus modestus) caused by nervous necrosis virus infection - Zhiqi Zhang; Yongxiang Yu; Chunyuan Wang; Zhen Meng; Yingeng Wang; Xiaojun Rong; Meijie Liao; Bin Li; Wenlong Li; Xinzhang Ji; Xiaoyan Cheng; Zheng Zhang (Aquaculture, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Tectonically driven erosion with climatic modulation across the southern Tibetan Plateau: Insights from 10Be erosion rates - Jia-Qi Sun; Jin-Gen Dai; Xu Han; Matthew Fox; Guang-Sheng Ren; Zhi-Cheng Yu; Bo-Rong Liu; Xiang-Rui Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Latitudinal gradients shape adaptive divergence of tea saponin accumulation in Camellia oleifera - Danmei Yu; Liyun Feng; Suyun Zhang; Xiaohua Liu; Huan Yang; Jie Xiao; Shang Chen; Xia Dong; Li Cheng; Yao Zhao; Jun Rong; Jian Zhang (Food Bioscience, 2026)

6H2L, a novel derivative of bifendate, dually suppresses glycolysis and glutaminolysis in hepatocellular carcinoma via inhibiting YAP stability - Beibei Zhang; Kaixuan Sheng; Yue Yan; Xinlei Wang; Xinning Cheng; Rong Liao; Zhiyi Yang; Mengyi Li; Fan Wang; Qi Qi; Yu Wang; Chenglin Li (Chemico-Biological Interactions, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Performance enhancement of cryogenic nitrogen ejectors for HEPS: a model-data dual-driven approach - Yu-Qing Wang; Ran Ding; Jia-Rong Zhang; Rui Ge; Chang-Cheng Ma; Yi Huo (International Journal of Refrigeration, 2026)

A case study on indoor air quality assessments and health risk implications across diverse university environments - Jheng Fong Tsai; Yu-Hsiang Cheng; Zong-Rong Chen; Chi-Chi Lin (Atmospheric Pollution Research, 2026)

Drying-wetting cycles alter the balance between physical fragmentation and leaching during leaf litter decomposition: a laboratory incubation experiment - Le-Lin Yu; Rui-Jing Chai; Qi-Han Tu; An He; Le-Cheng Ai; Rong Mao (Plant and Soil, 2026)

Polyprenylated acylphloroglucinols from Hypericum monogynum and their reversal of multidrug resistance in MCF-7/ADR cells - Yan-Rong Zeng; Peng Zhao; Jing-Yi Yin; Hong-Jin Ban; Zhan Feng; Yu-Xiang Li; Min Yang; Jing Tan; Cheng-Jian Tan; Jue Yang; Xiao-Jiang Hao; Chun-Mao Yuan (Molecular Diversity, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Introducing Double-Moment Warm Rain Physics into the Goddard 4ICE Microphysics Scheme - Kao-Shen Chung; Yu-Jyun Liou; Cheng-Rong You; Zhao-Cheng Zeng; Pay-Liam Lin; Donghai Wang; Wei-Kuo Tao; Stephen Lang; Takamichi Iguchi; Adrian Loftus; Jiun-Dar Chern (Asia-Pacific Journal of Atmospheric Sciences, 2026)
In this study, a new double-moment warm rain Goddard 4ICE scheme (GCEDM) is developed based on the Goddard 4ICE single-moment (GCESM) scheme and then tested using idealized 2D squall line and 3D supercell simulations. The addition of the total number concentrations for cloud water ( $$\:N_{TC}$$ ) and rainwater ( $$\:N_{TR}$$ ) enables this new scheme to simulate more diverse raindrop size distributions, making it more realistic. GCEDM has similar overall thermal and dynamic characteristics to GCESM but produces higher evaporation rates, predicted particle number concentrations, and mass mixing ratios than GCESM, leading to stronger cold pools than with GCESM. In addition, comparisons are made versus the Weather Research and Forecasting Model Double-Moment Microphysics 7-class scheme (WDM7), which was also improved from a single-moment 4-class ice scheme to a double-moment warm-rain scheme. WDM7 also shows a stronger cold pool, but the system characteristics and microphysical processes are quite different from the single-moment version of this scheme.

Seneca Valley virus 2B and 3 C proteins attenuate the cGAS-STING signaling pathway by targeting STING for degradation - Xuexia Wen; Meijun Zhou; Shijie Xie; Jin Yuan; Yu Hong; Ruiyi Ma; Liwei Zhao; Dan Wang; Rong Quan; Peipei Cheng; Jiangwei Song (Veterinary Microbiology, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Briarane-type diterpenes from a closed-system cultured soft coral Briareum stechei - Lo-Yun Chen; Bo-Rong Peng; Thanh Hao Huynh; You-Ying Chen; Yu-Cheng Chen; Ngoc-Thac Pham; Huong-Giang Le; Quoc-Vu Pham; Phuong Vu Luu; Ying-Mi Lai; Mohamed El-Shazly; Tsong-Long Hwang; et al. (Phytochemistry, 2026)

SMART-assisted discovery of scalaranes from the marine sponge Lendenfeldia sp. and its anti-osteoclastogenesis activity - Quoc-Vu Pham; Yu-Chia Chang; You-Song Cheng; Yun-Shiuan Chen; Lo-Yun Chen; Mei-Hsien Lee; Jui-Hsin Su; Bo-Rong Peng; Kuei-Hung Lai; Tsong-Long Hwang (Phytochemistry, 2026)

Precise pH control and synergistic interaction of raw materials improve the quality of stewed beef: multi-omics analysis of tenderization mechanisms and flavor restructuring - Yan Shen; Zezhu Du; Jinya Dong; Yuanfeng Chen; Huiqing Luo; Siyu Zhou; Cheng Gong; Shikuan Zhao; Zhiyu Li; Lihui Yu; Rong Geng; Xiaocui Du; et al. (Food Chemistry, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

Development and Evaluation of Antioxidant Postbiotics from Bacillus amyloliquefaciens C-1 to Alleviate DSS-Induced Colitis - Xinyao Hou; Jiayu Feng; Jiale Qin; Jianhui Mo; Rong Yu; Jia Lv; Shaoru Li; Jing Tian; Yue Cheng; Bei Han (Probiotics and Antimicrobial Proteins, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

New C22-related terpenoid from Formosan marine sponge Lendenfeldia sp. - Quoc-Vu Pham; Hsin-Wei Wang; Yu-Cheng Chen; Yu-Chia Chang; You-Song Cheng; Yun-Shiuan Chen; Mei-Hsien Lee; Jui-Hsin Su; Bo-Rong Peng; Kuei-Hung Lai (Phytochemistry Letters, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Overlooked role of soil microbial-derived carbon in promoting neurotoxic methylmercury production - Man Yang; Zhi-Cheng Hu; Hui-Wen Liu; Wen Zhang; Yun-Yun Hao; Qin Liu; Jia-Xuan Meng; Bo Meng; Qiaoyun Huang; Baohua Gu; Yu-Rong Liu (Journal of Hazardous Materials, 2026)

How human-perceived urban green spaces contribute to mental well-being: a machine learning approach - Enqi Cheng; Yuejing Rong; Yan Yan; Chenxing Wang; Lijie Wang; Yu Zhao; Zetong Wang; Wei Li (Journal of Environmental Management, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Microwave-enhanced carbothermal reduction for efficient recovery of valuable metals from spent lithium-ion batteries - Gui-Rong Zhang; Da-Shuai Li; Xing-Yu Huang; Yuan-Long Liu; Yan-Qing Cheng; Ling Tong (Waste Management, 2026)

Exhumation history of the eastern Tethyan Himalaya: Evidence from Apatite (U Th)/He Thermochronology - Xu Han; Jin-Gen Dai; Bo-Rong Liu; Zhi-Cheng Yu (Tectonophysics, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)